TINDAK TUTUR EKSPRESIF DALAM PERCAKAPAN GRUP WHATSAPP DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA - Rohmawati, Ari (JURNAL PESONA, 2018)
AbstractThis study aims to describe expressive speech acts of PMI Unila Volunteer Corps members in WhatsApp Group and its implications in Indonesian language learning. This research uses qualitative method. Expressive speech acts commonly used by the members of PMI Unila Volunteer Corps are inform of sympathy, condolence, praise, congratulations, apologies, and thank you. Speech act of sympathy represents volunteer help, compassion, and caring. Speech act ofÂ condolence represents sorrow, prayer, and loss. Speech act of praise represents appreciation, attention, and recognition. Speech act of congratulating represents the expression of success and joy. Speech act of apology represents worries and politeness. Speech act ofÂ thankful represents an appreciation, happiness, and flattery.Keywords : expressive speech act, WhatsApp Conversation, learning language of Indonesia